Peran Media Gambar Berseri Terhadap Kemampuan Menulis Karangan Siswa Kelas VI SD Negeri 28 Dompu Tahun Pembelajaran 2022/2023 - Marlina, Leni; Yusnarti, Mulya; Hasan, Hasan; Yulianti, Eka; Asmiyati, Suci (LPPM Institut Pendidikan Nusantara Global, 2024)
The problem that is answered in this research is, how is the role of serial image media on the ability to write essays of students of grade six elementary school 28 Dompu in the learning year 2022/2023. This thesis is descriptive research with a qualitative approach. Research conducted to describe or explain systematically, factually, accurately about the facts or phenomena being investigated. As for the informants who were the source of the data were theachers and sixth grade students. To obtain data, the author uses data collection techniques in the form of observation, interviews, and documentation. And triangulation as evidence of the validity of the data obtained by the outhor. Then the conclusion is: the role of serial image media is able to make students more active because it can encourage students to be able to express ideas, opinions, and imagination to tell stories, and serial image media makes it easier for students to find vocabulary and express the contents of the image in ward a systematic essay.